KAJIAN PEMBIAYAAN SAMPAH DAN KELEMBAGAAN UNTUK PENGELOLAAN TPA SAMPAH KOTA BLITAR - Parikesit Penangsang; Pramita Studiviany; Adiati Trihastuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Technological developments and population growth have an effect on waste management which requires proper and adequate handling because the volume of waste is increasing day by day. The main problem of final waste management is overcapacity at TPA and low level of waste management before entering TPA. The city of Blitar has an area of around 32.57 km2 with a population of ± 158,313 people. The Blitar City TPA is located in the Ngegong neighborhood, Gedog Village, Kec. Sananwetan with a land area of 4 ha. There are 2 cells in the prepared Gedog TPA. Currently cell 1 is passive. If the community and scavengers sort waste, it is estimated that cell 2 will be full in the next 3 years. The results of the calculation of the investment performance of the local government of Blitar City have a high investment capacity. Waste processing is still sourced from the Blitar city budget. The Operational Budget for Waste Handling from the APBD of the city of Blitar has fluctuated and there is not even written data on the budget. The fees from the community are not enough to manage all the existing waste, so they are unable to cover the operational costs of waste processing. The UPTD in the field of waste management has not yet collected user fees in a good administrative manner, because data on fees is not yet available according to the type of classification/group of objects of fees. It is recommended that personnel take part in administrative management training for collecting waste fees, so that they have a data base for fees. Regional Regulation Number 07 of 2017 concerning Garbage/Cleaning Service Charges needs to be amended, which will be used as the basis for imposing fees according to the type of object. Collaboration between the government and business entities in providing infrastructure for waste management in the city of Blitar cannot yet be carried out. It is better to do internal improvements, for example in financing and institutions.